Solve for a (complex solution)
\left\{\begin{matrix}\\a=x_{1}-x_{1}^{2}+x_{0}-x_{0}x_{1}-x_{0}^{2}\text{, }&\text{unconditionally}\\a\in \mathrm{C}\text{, }&x_{1}=x_{0}\end{matrix}\right.
Solve for a
\left\{\begin{matrix}\\a=x_{1}-x_{1}^{2}+x_{0}-x_{0}x_{1}-x_{0}^{2}\text{, }&\text{unconditionally}\\a\in \mathrm{R}\text{, }&x_{1}=x_{0}\end{matrix}\right.
Solve for x_0 (complex solution)
x_{0}=\frac{\sqrt{1-4a+2x_{1}-3x_{1}^{2}}-x_{1}+1}{2}
x_{0}=\frac{-\sqrt{1-4a+2x_{1}-3x_{1}^{2}}-x_{1}+1}{2}
x_{0}=x_{1}
Solve for x_0
\left\{\begin{matrix}\\x_{0}=x_{1}\text{, }&\text{unconditionally}\\x_{0}=\frac{\sqrt{1-4a+2x_{1}-3x_{1}^{2}}-x_{1}+1}{2}\text{; }x_{0}=\frac{-\sqrt{1-4a+2x_{1}-3x_{1}^{2}}-x_{1}+1}{2}\text{, }&a\leq -\frac{3x_{1}^{2}}{4}+\frac{x_{1}}{2}+\frac{1}{4}\end{matrix}\right.
Share
Copied to clipboard
x_{1}^{3}-x_{0}^{3}-x_{1}^{2}+x_{0}^{2}+a\left(x_{1}-x_{0}\right)=0
To find the opposite of x_{1}^{2}-x_{0}^{2}, find the opposite of each term.
x_{1}^{3}-x_{0}^{3}-x_{1}^{2}+x_{0}^{2}+ax_{1}-ax_{0}=0
Use the distributive property to multiply a by x_{1}-x_{0}.
-x_{0}^{3}-x_{1}^{2}+x_{0}^{2}+ax_{1}-ax_{0}=-x_{1}^{3}
Subtract x_{1}^{3} from both sides. Anything subtracted from zero gives its negation.
-x_{1}^{2}+x_{0}^{2}+ax_{1}-ax_{0}=-x_{1}^{3}+x_{0}^{3}
Add x_{0}^{3} to both sides.
x_{0}^{2}+ax_{1}-ax_{0}=-x_{1}^{3}+x_{0}^{3}+x_{1}^{2}
Add x_{1}^{2} to both sides.
ax_{1}-ax_{0}=-x_{1}^{3}+x_{0}^{3}+x_{1}^{2}-x_{0}^{2}
Subtract x_{0}^{2} from both sides.
\left(x_{1}-x_{0}\right)a=-x_{1}^{3}+x_{0}^{3}+x_{1}^{2}-x_{0}^{2}
Combine all terms containing a.
\left(x_{1}-x_{0}\right)a=x_{0}^{3}-x_{0}^{2}-x_{1}^{3}+x_{1}^{2}
The equation is in standard form.
\frac{\left(x_{1}-x_{0}\right)a}{x_{1}-x_{0}}=\frac{x_{0}^{3}-x_{0}^{2}-x_{1}^{3}+x_{1}^{2}}{x_{1}-x_{0}}
Divide both sides by x_{1}-x_{0}.
a=\frac{x_{0}^{3}-x_{0}^{2}-x_{1}^{3}+x_{1}^{2}}{x_{1}-x_{0}}
Dividing by x_{1}-x_{0} undoes the multiplication by x_{1}-x_{0}.
a=x_{1}-x_{1}^{2}+x_{0}-x_{0}x_{1}-x_{0}^{2}
Divide -x_{0}^{2}+x_{0}^{3}+x_{1}^{2}-x_{1}^{3} by x_{1}-x_{0}.
x_{1}^{3}-x_{0}^{3}-x_{1}^{2}+x_{0}^{2}+a\left(x_{1}-x_{0}\right)=0
To find the opposite of x_{1}^{2}-x_{0}^{2}, find the opposite of each term.
x_{1}^{3}-x_{0}^{3}-x_{1}^{2}+x_{0}^{2}+ax_{1}-ax_{0}=0
Use the distributive property to multiply a by x_{1}-x_{0}.
-x_{0}^{3}-x_{1}^{2}+x_{0}^{2}+ax_{1}-ax_{0}=-x_{1}^{3}
Subtract x_{1}^{3} from both sides. Anything subtracted from zero gives its negation.
-x_{1}^{2}+x_{0}^{2}+ax_{1}-ax_{0}=-x_{1}^{3}+x_{0}^{3}
Add x_{0}^{3} to both sides.
x_{0}^{2}+ax_{1}-ax_{0}=-x_{1}^{3}+x_{0}^{3}+x_{1}^{2}
Add x_{1}^{2} to both sides.
ax_{1}-ax_{0}=-x_{1}^{3}+x_{0}^{3}+x_{1}^{2}-x_{0}^{2}
Subtract x_{0}^{2} from both sides.
\left(x_{1}-x_{0}\right)a=-x_{1}^{3}+x_{0}^{3}+x_{1}^{2}-x_{0}^{2}
Combine all terms containing a.
\left(x_{1}-x_{0}\right)a=x_{0}^{3}-x_{0}^{2}-x_{1}^{3}+x_{1}^{2}
The equation is in standard form.
\frac{\left(x_{1}-x_{0}\right)a}{x_{1}-x_{0}}=\frac{x_{0}^{3}-x_{0}^{2}-x_{1}^{3}+x_{1}^{2}}{x_{1}-x_{0}}
Divide both sides by x_{1}-x_{0}.
a=\frac{x_{0}^{3}-x_{0}^{2}-x_{1}^{3}+x_{1}^{2}}{x_{1}-x_{0}}
Dividing by x_{1}-x_{0} undoes the multiplication by x_{1}-x_{0}.
a=x_{1}-x_{1}^{2}+x_{0}-x_{0}x_{1}-x_{0}^{2}
Divide -x_{0}^{2}+x_{0}^{3}+x_{1}^{2}-x_{1}^{3} by x_{1}-x_{0}.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}